Peek-a-boo! : in the night garden - Davenport, Andrew (BBC Children's London, 2010)
The Night Garden friends are playing hiding. Makka Pakka begins, and as he finds Upsy Daisy, Igglepiggle and others, they join him on his search. This board book has exciting flaps to lift and tactiles to feel on a journey through the Night Garden. It lets you lift the flaps on each spread to reveal who's hiding.